Morphologically indistinguishable hybrid Carassius female with 156 chromosomes: A threat for the threatened crucian carp, C. carassius, L - Knytl, Martin; Kalous, Lukáš; Rylková, Kateřina; Choleva, Lukáš; Merilä, Juha; Ráb, Petr (PloS one, 2018)
The crucian carp Carassius carassius (Linnaeus, 1758), is native to many European freshwaters. Despite its wide distribution, the crucian carp is declining in both the number and sizes of populations across much of its range. Here we studied 30 individuals of a putative pure population from Helsinki, Finland. Despite clear external morphological features of C. carassius, an individual was of a higher ploidy level than the others. We therefore applied a set of molecular genetic (S7 nuclear and cytochrome b mitochondrial genes) and cytogenetic tools (sequential fluorescent 4', 6-diamidino-2-phenylindole [DAPI], Chromomycin A3 [CMA3], C-banding and in situ hybridization [FISH] with both 5S and 28S ribosomal DNA probes) to determine its origin. While all examined characteristics of a diploid representative male (CCAHe2Fi) clearly corresponded to those of C. carassius, a triploid individual (CCAHe1Fi) was more complex. Phylogenetic analysis revealed that the nuclear genome of CCAHe1Fi contained three haploid sets: two C. gibelio and one C. carassius. However the mitochondrial DNA was that of C. gibelio, demonstrating its hybrid origin. The FISH revealed three strong (more intensive) 5S rDNA loci, confirming the triploid status, and an additional 24 weak (less intensive) signals were observed in the chromosome complement of CCAHe1Fi. On the other hand, only two strong and 16 weak 5S rDNA signals were visible on the chromosomes of the CCAHe2Fi male. 28S rDNA FISH revealed four strong signals in both CCAHe1Fi and CCAHe2Fi individuals. CMA3 staining revealed four to six CMA3-positive bands of CCAHe1Fi, while that of diploids contained only two to four. The fact that a polyploid hybrid Carassius female with a strong invasive potential may share morphological characters typical for endangered C. carassius highlights a need to combine genetic investigations of Carassius cryptic diversity with conservation measures of C. carassius in Europe.
Keywords: druhová specificita; Male; genetická variace; hybridizace in situ fluorescenční; fylogeneze; Endangered Species; Phylogeny; triploidie; Europe; kapři; karyotyp; mužské pohlaví; Species Specificity; Chromosome Banding; genetické markery; Evropa; Animals; ženské pohlaví; zvířata; pruhování chromozomů; Carps; Hybridization, Genetic; Diploidy; In Situ Hybridization, Fluorescence; Finsko; hybridizace genetická; Genetic Variation; Triploidy; Female; diploidie; Genetic Markers; Finland; Karyotype; ohrožené druhy